Mediating role of organisational justice on internal alignment and job performance among local employees in Jordan industrial estates - Mahmoud A, Khtatbeh Mohamed (2020)
Job performance is a significant factor that organisations seek to increase and maintain in order to achieve strategic goals. In pursuit of excellence, a firm must attract and maintain highly qualified, talented employees effectively and efficiently. In order to achieve this, it is necessary to study the factors that affect the recruitment of qualified employees and study the factors that affect their performance and satisfaction. Among these factors is how to build the internal job structure on which to determine the value of salaries and wages for employees. The industrial sector in Jordan is one of the most important sectors that is considered a crucial tributary of the economy and contribute to the employment of a rigorous number of Jordanian talents, which thus contributes to reducing the increased problem of unemployment. Jordan Industrial Estates Company (JIEC), a vital semi-governmental organisation, manages six qualified industrial estates in Jordan by providing infrastructure and basic work facilities to attract investors and establish factories there. Jordan Industrial Estates (JIE) contributes to raising the gross domestic product (GDP) in addition to its influence in reducing the unemployment rates. Therefore, investigating one of the human resource practices that play a vital role in raising the level of employees’ performance and retaining them was necessary, especially in JIE, where the percentage of Jordanian workers is decreasing compared to the total number of employees. This study assessed the causal relationships in internal alignment (job analysis, job evaluation and internal pay structure) as a major factor affecting job performance. Another subject of examination was the mediating role of organisational justice on the relationship between these factors and job performance in terms of employees’ perception of justice regarding decisions on setting wages and salaries and the fairness of these payments when compared to similar jobs. A review of literature and theories showed significant overlap in the structure and relationships of the factors and practices that affect job performance. This study examined the most essential of these factors related to how to determine employees’ salaries and wages, as well as the extent of its impact on their performance, in addition to conceptualise these factors in a framework that shows these relationships. This study aimed to investigate the mediating effect of organisational justice on the relationship between internal alignment and job performance. For that, the researcher based this study on the vital and significant conceptualisations of the equity theory and the pay model. This research employed a quantitative approach. The sample consisted of 690 Jordanian employees working in three industrial estates, chosen to represent the study population. Data were collected through a self-administrated questionnaire distributed to the study sample. Data analysis involved structural equation modelling (SEM) using Analysis of Moment Structures (AMOS) and Statistical Package for Social Sciences (SPSS) software tools. The results of this study revealed a significant positive effect of two of the independent variables, job analysis and internal pay structure, on job performance. In contrast, no significant effect of job evaluation on job performance was found. Moreover, the study demonstrated that organisational justice partially mediates the relationship between each of the factors of job analysis, internal pay structure and job performance. Meanwhile, full mediation between job evaluation and job performance was noted. In conclusion, the researcher believes that striving to raise and maintain the level of employees’ performance through practices that affect their lives is vital for organisations. One facet of this endeavour involves achieving justice through using job analysis and internally comparing similar jobs as part of the decision-making process that determines employee salaries and wages. This approach will motivate employees to improve their performance and enhance retention. The results of this study have many practical and theoretical contributions which have been discussed.